An enhancer of DNA replication. - Gennaro, M L (1988)
cmp, a nucleotide sequence element in the plasmid pT181 of Staphylococcus aureus, acts as an enhancer of DNA replication. When cmp is present on an unrelated vector along with the pT181 origin of replication, it increases the ability of the linked pT181 origin to compete with a coresident pT181 plasmid for the initiator protein RepC. cmp is contained within a 156-base-pair segment, and its deletion from pT181 reduces by twofold the frequency of plasmid replication under derepressed conditions. The enhancer sequence contains a locus of DNA bending, and enhancer activity decreases with distance from the replication origin.